Does Buddhism Accept the Third Sex Party? The Buddhist Notion on Different Sexual Orientations - Vijitha, Moragaswewe (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
This research explores Buddhism's perspective on the third gender, intersecting religious cultural, and sexological studies. In many religions, sexual intercourse outside heterosexual norms is often viewed as sinful, especially within celibate contexts. Buddhism offers a unique view, seeing kāma taṇhā (sensual desire) as a barrier to overcoming Samsāric existence. True liberation in Buddhism transcends gender, aiming for freedom from psychological afflictions (greed, hatred, delusion). Buddhistic ethics accommodate sexual diversity, including LGBTIQA individuals, advocating non-discriminatory practice. This research, based on textual studies of primary Buddhist teachings and secondary scholarly texts, focuses on early discourses and gender-based myths in the Theravāda tradition. The study seeks to highlight Buddhism's rational humanist aspects to support LGBT social liberation. Findings show Buddhism respects and recognizes human sexual orientation's natural diversity. Historical Buddhist texts document various sexual behaviors—heterosexuality, homosexuality, and intersexuality—as natural phenomena, not marginalization conditions. Additionally, Buddhism promotes an inclusive society free from gender discrimination, emphasizing equality and advocating for compassionate, non-dogmatic human rights approaches. Buddhist teachings highlight that moral and spiritual progress is gender-independent, aligning with modern humanistic values. Conclusively, Buddhism embraces freedom, diversity, and equality, supporting LGBT rights and dignity, and advocating for a society beyond inequality and discrimination.